1998
DOI: 10.21273/hortsci.33.3.450d
|View full text |Cite
|
Sign up to set email alerts
|

Wildflower Seed Source Affects Performance of Six Wildflower Species

Abstract: Field plantings of six native wildflower species were established at five sites in 1997 from seeds derived from local native populations (local ecotype) and from seeds purchased from commercial sources outside of Florida (nonlocal ecotype). The species were Cassia fasciculata (partridge-pea), Coreopsis lanceolata (lance-leaf coreopsis), Gaillardia pulchella (blanketflower), Ipomopsis rubra (standing cypress), Rudbeckia hirta (black-eyed susan), and Salvia lyrata (lyre-leaf sage; cancer weed). They were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…Although the ecotype data used in our model were simply shared source habitat rather than a measure of true genetic relationship, the importance of inherited traits in populations of species that are adaptations to the ecological conditions of the source habitat is well-documented (Grime 2001;Houseal & Smith 2000;Ratcliffe 1961). Many plant species have widespread distributions covering different habitats or even ecoregions, and plants or seeds from dissimilar habitats may not perform as well as those from shared ecotypes or local populations (Gordon & Rice 1998;Kindell et al 1996;Norcini et al 1998).…”
Section: Ecotypesmentioning
confidence: 99%
“…Although the ecotype data used in our model were simply shared source habitat rather than a measure of true genetic relationship, the importance of inherited traits in populations of species that are adaptations to the ecological conditions of the source habitat is well-documented (Grime 2001;Houseal & Smith 2000;Ratcliffe 1961). Many plant species have widespread distributions covering different habitats or even ecoregions, and plants or seeds from dissimilar habitats may not perform as well as those from shared ecotypes or local populations (Gordon & Rice 1998;Kindell et al 1996;Norcini et al 1998).…”
Section: Ecotypesmentioning
confidence: 99%
“…Differences in responses to biotic and abiotic stresses as affected by seed source have been noted for other native wildflower species grown under Florida conditions. Greater incidence of disease and/or foliar decline occurred on lanceleaf coreopsis (Coreopsis lanceolata) and lyreleaf sage (Salvia lyrata) derived from non-Florida seed sources compared to Florida ecotypes (Norcini et al, 1998). In a later study (Norcini et al, 2001a), percent survival of a Florida ecotype of lyreleaf sage was higher than the non-Florida selection.…”
mentioning
confidence: 97%
“…This selection process and the identification of known ecotypes of the species (Beckwith, 1991;Celik, 1996;Norcini et a1., 1998) may have affected how well specific lines perform under differing environmental conditions. Norcini et al (1998Norcini et al ( , 2001b reported that a northern Florida ecotype and a central Florida selection from a native population survived longer under Florida conditions [American Horticultural Society (AHS) Heat Zone 9; USDA Hardiness Zone 8b] than a commercially produced selection from Texas. None of the Texas plants survived through October (most did not survive through September), whereas 60% and 90% of northern Florida and central Florida plants were still alive in October, and 20% and 90% of northern Florida and central Florida plants, respectively, were alive in November when the experiment was terminated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…O ver the past 10 to 20 years, production of prevariety germplasm of native wildflower seeds has risen dramatically in response to the demand for site-or regionally specific ecotype seeds for roadside plantings as well as for ecological restoration and revegetation projects (Booth and Jones, 2001;Harper-Lore and Wilson, 1999;Houseal and Smith, 2000). Researchers and practitioners realize that survival, growth, and flowering of native wildflower species can be strongly affected by seed origin (Marois and Norcini, 2003;Norcini et al, 1998Norcini et al, , 2001. Demand for prevariety germplasms is being met by a niche industry that is primarily in the midwestern and western United States (Booth and Jones, 2001;Houseal and Smith, 2000).…”
mentioning
confidence: 99%